Studi Fenomenologi: Minat Siswa SMK Melanjutkan Studi Ke Perguruan Tinggi - Chrestella Putu Holy Kusuma; Mohammad Khasan (LPPM Institut Pendidikan Nusantara Global, 2026)
The low interest of vocational high school (SMK) students in continuing their studies to higher education is a problem influenced by various internal and external factors. This study aims to deeply understand the factors affecting SMK students' interest in pursuing higher education. The research employed a qualitative approach with a phenomenological design. The research subjects were three twelfth-grade SMK students in the Kudus Regency area, selected purposively, consisting of NP (female, 17 years old), DN (male, 18 years old), and RF (male, 18 years old). The results showed that students' interest varied: NP demonstrated weak interest due to the dominance of work orientation and economic pressure; DN possessed strong internal interest but was hindered by economic factors; RF exhibited stable and directed interest because of family support and high internal motivation. The influencing factors included concentration of attention, curiosity, motivation, needs, family, peer groups, and environment. In conclusion, SMK students' interest in continuing their studies to higher education is determined by a complex interaction between internal and external factors, with family support and self-motivation being the most dominant factors.